Sound, noise and speech at the 9000-seat Holy Trinity Church in Fatima, Portugal - António P. O. Carvalho (2010)
This paper presents the interior acoustical characterization of the 9,000-seat church of the Holy Trinity in the Sanctuary of Fátima, Portugal, inaugurated in 2007. In situ measurements were held regarding interior sound pressure levels (with and without the HVAC equipment working), NC curves, RASTI (with and without the installed sound system) and reverberation time. The results are presented and commented according to the design values. A comparison is made with other churches in the world also with a very large volume (for instance the Basilica Mariacka in Gdask). The measured data are also used to calculate a global index of this church acoustic quality using Engel and Kosalas Index Method.